(untitled) (Journal of Informatics and Mathematical Sciences, 2013)
Zayanderood is one of the most important river of Iran from west to east. The river source is located in Koohrang Mountains. The river passes through two provinces, Chaharmahal-Bakhtiary and esfahan. The river at the end discharges to the Govkhooni wetland. The river water is used for drinking, industrial and agricultural purposes. The determination of pollutants as heavy metals and other chemical parameters throughout the river is important and has a great role in the control of ecological condition of water media. The anthropogenic impact on the environment in the last four decade has proven to be extremely negative due to the quick development of industry. In the present work, ICP-MS as a multi-elemental technique has been used for the determination of heavy metals. The concentration of heavy metals in different stations of this river was different. The analysis shows the critical points of the river and also shown the points that continuous control should be done. In this paper, using multiple attribute decision making (MADM) is proposed. MADM problem is management science technique, which is popularly used to rank the priority of alternatives with respect to their competing attributes. Weights from the core of MADM: it is obvious that different weight lead to various evaluation results and decisions. The proposed model is applied for finding the best option from all the feasible alternatives.